Evaluation of Liquefaction Potential Index and Severity Mapping for Rangpur City Corporation (Journal of Science and Technology Research, 2023)
This paper aims to investigate the Liquefaction Potential Index (LPI) of different Wards and prepare a liquefaction severity map of Rangpur City Corporation. A Liquefaction severity map of a city helps the legislators and policymakers with informed land use planning as well as the development of the town. Disturbed soils from 10 Wards among 33 Wards of Rangpur were collected for different depths in a single borehole. The locations for the borehole were selected based on the seismic soil profile and engineering geology reports available for Rangpur City Corporation in CDMP-II. Standard Penetration Test (SPT) and Microtremor test were done on the field. Then, the Grain Size Distribution test and Liquefaction Potential Index (LPI) were determined for the collected samples in the laboratory. Based on the results of the tests done in the field and laboratory, the severity was classified as moderate, moderate to severe, and severe. Based on the Liquefaction Potential Index (LPI) value, four Wards of Rangpur City Corporation fall within the moderate risk class, three Wards show moderate to severe risk of liquefaction, and the remaining 3 Wards belong to the severe risk class.J. of Sci. and Tech. Res. 4(1): 49-58, 2022